The long winding road of opioid substitution therapy implementation in South-East Asia: challenges to scale up - Reid, G.; Higgs, Peter; Sharma, M. (PAGEPress, 2014)
In South-East Asia Region (SEAR) there were an estimated 400, 000 - 500,000 people who inject drugs (PWID). HIV prevalence among PWID was commonly 20% and higher in Indonesia, Thailand, Myanmar, and some regions of India. Opioid substitution therapy (OST) has been implemented as an important HIV prevention intervention in the Region. Various key challenges and barriers to scale up of OST exist: pervasive stigma and discrimination towards PWID; crimilization of drug use overshadowing a public health response; lack of political will and national commitment; low financial investment; focus towards traditional treatment model of detoxification and rehabilitation; low dose of OST; and poor monitoring and evaluation of programmes.Local evidence has highlighted that OST can be successful within the Asian context. Such evidence should be utilized more widely to advocate for policy and increased political commitment to ensure OST reaches a substantial greater number of drug users than currently exists.